Output Costs of Education and Skill Mismatch - Pietro Garibaldi; Pedro Maia Gomes; Thepthida Sopraseuth (Institute of Labor Economics (IZA), 2020)
We propose a simple theory of under- and over-employment. Individuals of high type can perform both skilled and unskilled jobs, but only a fraction of low-type workers can perform skilled jobs. People have different non-pecuniary values over these jobs, akin to a Roy model. We calibrate two versions of the model to match moments of 17 OECD economies, considering separately education and skills mismatch. The cost of mismatch is 3% of output on average but varies between -1% to 9% across countries. The key variable that explains the output cost of mismatch is not the percentage of mismatched workers but their wage relative to well-matched workers.
Keywords: E24; J24; 330; education mismatch; skill mismatch